Evaluation of Antioxidant Activities and Active Compounds Separated from Water Soluble Extracts of Korean Black Pine Barks - Shen, ChangZhe; Jun, HongYoung; Choi, SungHo; Kim, YoungMan; Jung, EunJoo; Oh, GiSu; Joo, SungJin; Kim, SungHyun; Kim, IlKwang (WILEY-V C H VERLAG GMBH, 2010)
Black pine barks from the southern region of Korea were extracted using pressurized hot water and the water soluble extracts were then separated in a stepwise fashion using a variety of solvents, column chromatography (CC), thin layer chromatography (TLC), and high pressure liquid chromatography (HPLC). The antioxidant activities of each fraction and the active compounds were determined based on the radical scavenging activities of 2,2-diphenyl-1-picrylhydrazyl (DPPH), reductive potential of ferric ion, and total phenol contents. A DPPH test showed that the half maximal effective concentration (EC50 value : 6.59 +/- 0.31 mu g/mL) of the ethyl acetate fraction (ca. 0.67%) was almost the same as that of the control compounds and inversely proportional to the value of the total phenol contents. The cell viability of the water extracts was confirmed by methyl thiazol-2-yl-2,5-diphenyl tetrazolium bromide (MTT) with enzyme linked immune sorbent assay (ELISA). Catechin, epicatechin, quercetin and ferulic acid were isolated from the ethyl acetate fraction as active compounds and identified by nuclear magnetic resonance. The antioxidant activity as value of DPPH of each of the separated compounds was lower than the ethyl acetate fraction, and ferulic acid was the lowest among these compounds.